Research hot topics and frontiers in social anxiety over the past decade: a CiteSpace bibliometric analysis based on Web of Science database from 2013 to 2023 - Zhang, Peng; Wang, Mingliang; Ding, Lin; Zhang, Jianing; Yuan, Yuqing; Tian, Xin (Frontiers in Psychiatry, 2024)
Objective: To understand the current study of social anxiety(SA) over the past decade, and to analyze the research hot topics and frontiers in this field. Methods: CiteSpace 6.2.R3 was used to analyze the literature on SA collected in the Web of Science core Collection database from 2013 to 2023.Results: A total of 9940 literatures were included after the screening, and the annual publication volume showed a steady increase. The results emphasize that Zvolensky MJ, Pine DS, and Heimberg RG are important authors in the field of SA. The largest number of publications in the United States and the institution that contributed most to the number of publications was the University of California System. Research hotspots are cognitive impairment, risk factors, complications, neuroimaging, and intervention strategies. SA related to the"theory of mind", "bullying victimization", "mobile phone", "network analysis", "technology" and "satisfaction are emerging research foci.This study identifies the current situation and trends of SA research, and provides a reference for future research topics and directions.